Green Human Resource Management and Employee Green Behavior: The Mediating Role of Environmental Commitment - Eka Rakhmat Kabul (Greenation International Journal of Tourism and Management, 2025)
The growing emphasis on environmental sustainability has encouraged organizations to integrate green principles into their human resource management practices. This study aims to examine the effect of Green Human Resource Management (GHRM) on Employee Green Behavior (EGB), with Environmental Commitment serving as a mediating variable. Drawing on Social Exchange Theory and the Ability–Motivation–Opportunity (AMO) framework, this research proposes that environmentally oriented HR practices can foster employees’ commitment to environmental values, which in turn encourages pro-environmental behavior in the workplace. A quantitative research design was employed using a survey method. Data were collected from 320 employees working in manufacturing and service organizations. The measurement model and structural relationships were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that GHRM practices have a significant positive effect on Employee Green Behavior. Furthermore, Environmental Commitment was found to have a significant positive impact on Employee Green Behavior and partially mediates the relationship between GHRM and Employee Green Behavior. These findings contribute to the green HRM literature by empirically validating the mediating role of Environmental Commitment in explaining how GHRM influences employee behavior. From a practical perspective, the study highlights the importance of embedding environmental values within HR policies such as green recruitment, green training, and green performance management to strengthen employees’ environmental commitment and promote sustainable behavior. This research offers valuable insights for managers seeking to enhance organizational sustainability through human resource strategies, particularly in emerging economy contexts.